The Use Of ELSA Speak in Improving English Speaking Skills at Tenth Grade Students of SMK Muhammadiyah Pagaralam - Nabila A'zahra Kosasih; Kurnia Febianti; Yuliana Yuliana (PT. Intelek Cendikiawan Nusantara, 2025)
The objective of this study was to examine the effectiveness of the ELSA Speak application in enhancing students’ English speaking skills. The research was conducted at SMK Muhammadiyah Pagaralam with a population of 404 students. Two tenth-grade classes were selected, consisting of an experimental group and a control group, each with 33 students. This study applied a quantitative method using a quasi-experimental design, with pre-tests and post-tests as data collection instruments.The results of the paired sample t-test showed that both groups improved after the treatment, but the experimental group improved more significantly. The mean post-test score of the experimental group was 70.73, while the control group scored 65.03, with a mean difference of 5.697. The independent sample t-test indicated that the t-obtained value was 4.217 with a degree of freedom (df) of 64. The t-table value at a 0.05 significance level was 2.000. Since the t-obtained value was higher and the significance level (0.000) was lower than 0.05, the alternative hypothesis (Ha) was accepted. This means there was a significant difference between the two groups, while the null hypothesis (H₀) was rejected. In conclusion, the ELSA Speak application significantly improved the English speaking skills of tenth-grade students at SMK Muhammadiyah Pagaralam.